PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sub Sektor Properti Dan Real Estate Di BEI Periode 2018-2020) - Yulinda Putri; Triyono Triyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze whether there is an influence between liquidity, profitability, sales growth, leverage, and activity ratios on firm value in the Property and Real Estate Sub-Sector companies listed on the IDX for the 2018-2020 period. The population of this research is all property and real estate companies listed on the IDX for the 2018-2020 period, totaling 174 companies. The sampling technique used is the purposive sampling method, which obtained 122 companies as research samples for three years of observation (2018-2020). Multiple linear regression analysis was used as data analysis. The results revealed that profitability, sales growth, leverage, and activity ratios had an effect on firm value, while liquidity had no effect.